Sex and age-specific survival and life expectancy in a free ranging population of Indri indri (Gmelin, 1788). Issue 1 (1st January 2021) - Rolle, F.; Torti, V.; Valente, D.; De Gregorio, C.; Giacoma, C.; Von Hardenberg, A.
Abstract: The critically endangered indri ( Indri indri ) is the largest extant lemur species and its population size is projected to decline over the next three generations due to habitat loss, hunting and climate change. Accurate information on the demographic parameters driving the population dynamics of indri is urgently needed to help decision-making regarding the conservation of this iconic species. We monitored and followed the life histories of 68 individually recognizable indris in 10 family groups in the Maromizaha New Protected Area (Madagascar) for 12 years. We estimated age and sex-specific survival trajectories using a Bayesian hierarchical survival model and found that the survival curves for male and female indris show a similar pattern, consistent with what found typically in primates; i.e., a high infant mortality rate which declines with age in the juvenile phase and increases again for adults. Also, life expectancies at 2 years of age (e2), were found to be similar between the sexes (e2 females = 7.8 years; e2 males = 7.5 years). We suggest that the lack of strong differences in the survival patterns for male and female indris are related to the strictly monogamous mating system and the lack of sexual dimorphism in this species. Our study provides, for the first time, robust estimates for demographic parameters of indris and one of the very few datasets on survival trajectories available for primates.